CHARACTERISTICS OF INDOOR RADON AND THORON CONCENTRATIONS IN CAVE DWELLINGS IN GANSU PROVINCE, CHINA. Issue 3 (16th May 2019) - Sorimachi, A; Tokonami, S; Omori, Y; Janik, M; Iwaoka, K; Ishikawa, T; Sun, Q
Abstract: Short-term measurements were made in four different types of Chinese cave dwellings, 'ground', 'open-cut', 'aboveground' and 'underground', located in Gansu Province, China, in order to evaluate the diurnal and seasonal variations in indoor radon ( 222 Rn) and thoron ( 220 Rn) concentrations. As a result, in most of the 'ground' and 'open-cut' cave dwellings in summer, the indoor 222 Rn concentrations during the nighttime were higher than those during the daytime. In the winter, such fluctuation was not observed. The daily indoor 222 Rn concentrations in summer were higher than those in winter, excluding the 'aboveground' cave dwelling, and these concentrations depended on dwelling type, exhalation from the building materials and ventilation. In contrast with 222 Rn, there seemed to be only very slight clear variations in 220 Rn.